The linguistic design of foreign German press texts represented in the youth magazine “Antidotum” - Pelka, Daniela (Papers in Linguistics, 2024)
The German minority in Poland makes extensive use of the opportunities offered by the modern media to preserve their linguistic-cultural autonomy and to transmit values important for their identity to the next generations. An important role among the employed media is played by the press, with one of its branches, i.e. the youth press. The linguistic design of articles published in the youth magazine “Antidotum” is determined primarily by the fact that they are written by young people for young people in a minority situation. The aim of the study is to show linguistic characteristics and peculiarities of this design and to relate them to the context in which the magazine is created and received.